Body temperature triggered customized patterned thermo-sensitive hydrogel for information storage and display. (28th September 2019) - Zhang, Yulin; Li, Yueshan; Chen, Kaixuan; Ma, Zixun; Wang, Xiangdong; Shi, Lingying; Ran, Rong
Abstract: With the rapid development of mobile networks and smartphones, quick response (QR) code has been more and more applied to various fields. Many individuals also have a QR code containing their own information. But because of its low cost and easy imitation, the QR code not only facilitated people's life but also brought the risk of revealing personal privacy. Therefore, it is very necessary to improve the security of the QR code by some simple encryption methods. Herein, by combining self-healing hydrogel and thermos-sensitive hydrogel, multifunctional dual network hydrogel with good mechanical properties, self-healing ability, and fast temperature sensitivity was synthesized. Moreover, customized patterned thermos-sensitive hydrogels can be obtained by the simple assembly. And the patterns can be triggered by human body temperature and disappeared after cooling at room temperature. Based on these performances, a QR code hydrogel with low cost, accessibility, durability and security features was fabricated for the storage and display of information. And this simple strategy is of universal significance for the synthesis of multifunctional and high-performance hydrogels. Graphical abstract: Image 1 Highlights: Hydrogels with high strength, good self-healing ability, and thermos-sensitivity were synthesized. Thermos-sensitivity of the hydrogel can be triggered by human body temperature. Assembly and remodeling give hydrogels the ability to form custom patterns. A simple thermos-sensitive encrypted quick response code hydrogel was developed.